2016
DOI: 10.1111/jam.13091
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for markerless genetic modifications in Azotobacter vinelandii

Abstract: This study demonstrates the successful application of a counter-selection approach to yield markerless genetic modifications to A. vinelandii, which should be of interest for a range of applications in this important model bacterium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The construction of A. vinelandii strain AZBB163, which is deregulated for nitrogen fixation and produces enhanced levels of ammonium in the growth medium, was previously described (4,10,12). The construction of a strain lacking the ability to synthesize polyhydroxybutyrate (AZBB131) was described previously (38). A. vinelandii strains AZBB326 and AZBB328 were constructed as detailed in Table 1, by transforming AZBB163 with the plasmids described in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…The construction of A. vinelandii strain AZBB163, which is deregulated for nitrogen fixation and produces enhanced levels of ammonium in the growth medium, was previously described (4,10,12). The construction of a strain lacking the ability to synthesize polyhydroxybutyrate (AZBB131) was described previously (38). A. vinelandii strains AZBB326 and AZBB328 were constructed as detailed in Table 1, by transforming AZBB163 with the plasmids described in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that if the amtB gene were deleted, it might result in a higher rate of ammonium accumulation within the supernatant. Using a strain from a previous report [11,26], the nifL deletion that results in extracellular ammonium accumulation was added to a strain containing the amtB deletion, creating A. vinelandii strain AZBB281. When evaluated for ammonium production, our results demonstrated that AZBB281 accumulated ammonium in the supernatant at a faster rate as compared to AZBB163 at both day 2 and day 3 ( Fig.…”
Section: Disruption Of a Futile Cycle Associated With Ammonium Importmentioning
confidence: 99%
“…Detailed methods for the transformation of A. vinelandii have been described previously [26,42]. Transformation of A. vinelandii DJ in order to modify target genes utilizing double homologous recombination with the pyrF counter-selection technique were implemented as described previously [11,26]. Details for strains constructed for use in this study are provided in Table 3.…”
Section: Genetic Constructs Gene Deletion and Confirmationmentioning
confidence: 99%
See 1 more Smart Citation
“…vinelandii DJ is a very well-studied obligate aerobe with an unusual metabolism that allows nitrogen fixation at atmospheric conditions . It is an exceptional model due to its natural competency under metal-starved conditions as well as expression of three different nitrogenase enzymatic complexes (MoFe, VFe, and FeFe cores). It was used previously to elucidate the structure , of the nitrogenase enzyme complex. Using homologous recombination with antibiotic selection, as well as sacB counterselection, A.…”
Section: Introductionmentioning
confidence: 99%